The University of Groningen in the World A Concise History. - van Berkel, Klaas (Amsterdam University Press, 2021)
The University of Groningen, situated in the northern part of the Netherlands, is a top-100 university with a distinguished history that dates back to 1614. Over the centuries it evolved, with ups and downs, from a small provincial and confessional university into a large, internationally oriented institution of higher education with a strong track record in scientific research and scholarship. This history is followed up to the present, which saw a remarkable recent surge in internationalisation in both research and education. The thesis underlying the story is that the internationalization of higher education in Groningen, and in the Netherlands at large, is in fact nothing but a return to a situation that existed during the seventeenth and eighteenth centuries, when both the professors and the students were to a large degree recruited from abroad. The story ends with a short paragraph on the impact of the corona crisis.